Keanekaragaman Jenis dan Potensi Pemanfaatan Tanaman Obat di Pekarangan Rumah Kalibata Pulo, Jakarta Selatan - Muliyah, Evi; Huda, Nuril; Putri, Nurhaliza Alya (Journal of Natural Sciences, 2024)
This study aims to explore the diversity and potential utilization of medicinal plants in home gardens in Kalibata Pulo. Medicinal plants in the yard can be used immediately when needed. The method used was a field survey in twelve residents' yards and interviews. The survey results identified fourteen types of medicinal plants used, including salam (Syzygium polyanthum), binahong (Anredera cordifolia), kelor (Moringa oleifera), aloe vera (Aloe vera), pandan (Pandanus amaryllifolius), suji (Dracaena angustifolia), tapak dara (Vinca rosea), insulin (Smallanthus sonchifolius), red betel (Piper ornatum), green betel (Piper betle), noni (Morinda citrifolia), lemongrass (Cymbopogon citratus), turmeric (Curcuma longa Linn), and kencur (Kaempferia galanga). These plants have various benefits, such as treating coughs, external wounds, diabetes, rheumatism, and fever. The parts commonly used are leaves, but some also use roots, flowers, fruits, and rhizomes. The utilization can be in the form of beverages or direct application, such as aloe vera gel.